2018
DOI: 10.17221/225/2017-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation, antioxidant and inhibitory activity of Thai mango seed kernel extracts

Abstract: Mango seed kernel extracts (MSKE) from Kaew and Choke-Anan mango cultivars were fractionated using Sephadex LH-20 column chromatography. Antioxidant activity and the inhibitory effects on tyrosinase, 5-lipoxygenase, hyaluronidase and α-glucosidase of MSKE fractions were evaluated. The key components of polyphenol, found in the most active fraction, were identified using LC-ESI-MS. Three major isolates were obtained from both cultivars of the MSKE with the absorb­ance being higher for Choke-Anan than Kaew. Frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…[56] reported that the pentagalloyl glucoside from mango peels possessed potent scavenging effects on hydroxyl radicals, superoxide anions, and singlet oxygen. Namngam et al [57] isolated different phenolic fractions from kernels of ‘Kaew’ and ‘Choke-Anan’ cultivars from Thailand. They observed that the rich fraction of galloyl glucosides (particularly tetragalloyl glucoside and hexagalloyl glucoside) exhibited the highest free radical scavenging activities as well as inhibitory effects against oxidation process mediated by enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…[56] reported that the pentagalloyl glucoside from mango peels possessed potent scavenging effects on hydroxyl radicals, superoxide anions, and singlet oxygen. Namngam et al [57] isolated different phenolic fractions from kernels of ‘Kaew’ and ‘Choke-Anan’ cultivars from Thailand. They observed that the rich fraction of galloyl glucosides (particularly tetragalloyl glucoside and hexagalloyl glucoside) exhibited the highest free radical scavenging activities as well as inhibitory effects against oxidation process mediated by enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Silva et al, reported in 2020 from mono-to penta-galloyl hexosides in different parts (petals, stalks, and nectar) of C. hypocistis [24]. However, all these compounds were previously reported in other sources such as Magnifera indica L. kernels and peels [25,26], Rhodiola crenulate roots [27], Rhodiola rosea roots, leaves, stems and flowers [27], Paeonia plants [28], and Pistacia vera leaves [29], among others [30]. Table 1 shows that a major number of these gallotannins were found in ethyl acetate, ethanol, water/ethanol, and water extracts.…”
Section: Characterization Of Polar Bioactive Compounds From C Hypocis...mentioning
confidence: 98%
“…Choke-Anan at the stage of maturity of around 110 days after the fruits were set, were obtained from an orchard in Nakornratchasima province, Thailand. Peel and pulp were removed from the fruits and the seeds were washed and stored at -18 o C. The preparation of mango seed kernel extract (MSKE) was done according to the method of Namngam et al [5]. A 50 g sample was blended with 500 ml of 95% ethanol for 5 min in a blender (Moulinex, Mexico), then incubated in a sonication bath (JAC Ultrasonic 2010P; Jinwoo Engineering Co., Ltd., Korea) at 20 KHz and 25°C for 15 min, followed by another incubation in a water bath at 80°C for 1 h. The mixture was cooled and filtered through a filter paper and then evaporated in a rotary evaporator (Büchi Rotavapor R II; USA) at 50°C under vacuum to get an extract with 70% solids.…”
Section: Preparation Of Mango Seed Kernel Extracts (Mske)mentioning
confidence: 99%
“…The phenolic constituents of mango seed kernel and their bioactivities including antioxidant activity have been extensively reported [2,3]. The strong in vitro antioxidant properties and active phenolic components of Thai mango seed kernel extract (MSKE) from Kaew and Choke-Anan cultivars has previously been shown [4,5]. In addition, the application of MSKE as a natural antioxidant used to protect against oxidation in sunflower seed oil under accelerated storage [6] and in bologna-type meat products during refrigerated storage [7] has been reported.…”
Section: Introductionmentioning
confidence: 99%